RESPONSE OF POMEGRANATE TREES CV. SAWA TO Foliar Application with NPK fertilizer and LICORICE ROOT EXTRACT - Darwan Hasan; Jehad Kader (مجلة جامعة كركوك للعلوم الزراعية)
The experiment was conducted during the growing season of 2021 on twelve-year old Sawa pomegranate trees (Punica granatum L.) in a local orchard in Darashakran - Erbil Governorate, Kurdistan - Iraq, to study the effect of foliar spray of Four levels with NPK (10-10-40) (0 , 1 , 2 , 3 g.l-1) and three levels of licorice root extracts (0 , 5 , 10 g.l-1) and their interactions on growth and yield of pomegranate trees, and all selected trees sprayed twice, The first foliar spray of NPK was on 17/May/ 2021 after two weeks of complete fruit set, at 6 AM. and second spray of NPK was on 23/July/2021 when the fruit pill was changed in color. Also The first foliar of licorice root extract was performed on 18/May/2021 after two weeks of complete fruit set, and the second spray was conducted on 24/July/2021 when the fruit pill was changed in color. The study applied as a factorial experiment in Randomized Complete Block Design (RCBD) with three replications by using one tree as the experimental unit thus the number of trees will be used in this study (4 x 3 x 3 = 36 trees). The results showed that the most incremental application and the interaction between NPK and Licorice root extracts rates especially at high concentrations, (3 g.l-1 NPK and 10 g.l-1 Licorice root extracts) led to significant increase and gave the highest value of the most of the studied characteristics, leaf content of nitrogen, phosphor and potassium 2.493 %, 0.150 % and 1.192 % respectively, tree yield 77.38 kg, juice percentage 29.500 %, TSS/T.A ratio 34.675%, anthocyanin mg.100 ml-1 13.370, and Vit-C mg.100 ml-1 13.363